A New Bis‐(NHC)‐P(II) Complex Supported on Magnetic Mesoporous Silica: An Efficient Pd(II) Catalyst for the Selective Buchwald‐Hartwig Monoarylation of Ammonia. Issue 13 (4th April 2023) - Fekri, Somayeh; Mansoori, Yagoub; Esquivel, Dolores; Navarro, M. Angeles
Abstract: We report the synthesis and identification of a new bis(NHC)‐Pd(II) catalyst supported on magnetic SBA‐15 (Fe3 O4 @SBA‐15). The surface of magnetic SBA‐15 was subsequently treated with (3‐aminopropyl) triethoxysilane (APTES), cyanuric chloride (CC), imidazole, and 2‐bromopyridine. The modified magnetic mesoporous material was then further treated with separately prepared trans‐ [Pd(Cl)2 (SMe2 )2 ] complex to give Fe3 O4 @SBA‐AP‐CC‐bis(NHC)‐Pd(II) as a supported bis(NHC)‐Pd(II) complex. The catalyst was fully characterized by common spectroscopic methods. X‐ray photoelectron spectroscopy (XPS) revealed that some imine nitrogens interact with palladium atoms. The supported Pd(II) complex catalyzed the direct monoarylation of ammonia with iodo‐, bromo‐, and chloroarenes, selectively. The effects of reaction components and parameters were investigated to establish the optimal reaction conditions. The catalyst was separated by a magnet, washed, and applied in the subsequent run. It exhibited noticeable stability and reused over seven catalytic cycles with negligible deactivation. A small Pd leaching (1.04 %) was observed in the first run. Abstract : The present work, describes functionalization of magnetic mesoporous silica (Fe3 O4 @SBA‐15) by a bis(NHC)‐Pd(II) complex. The obtained supported catalyst was applied in the monoarylation of ammonia with haloarens. The catalyst was fully characterized, and the reaction conditions including the ammonia concentration, the solvent, temperature, and the catalyst dosage were optimized. The catalyst can be retrieved magnetically and reused for at least seven times without significant loss of activity.